2020
DOI: 10.5194/esd-2020-83
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Labrador Sea sub-surface density as a precursor of multi-decadal variability in the North Atlantic: a multi-model study

Abstract: Abstract. The Subpolar North Atlantic (SPNA) is a region with prominent decadal variability that has experienced remarkable warming and cooling trends in the last few decades. These observed trends have been preceded by slow-paced increases and decreases in the Labrador Sea density (LSD), which are thought to be a precursor of large scale ocean circulation changes. This article analyses the inter-relationships between the LSD and the wider North Atlantic across an ensemble of coupled climate model simulations.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…While many AMOC anomalies remain localized, some are communicated meridionally, giving rise to large-scale AMOC variations. Large-scale AMOC anomalies are thought to be generated in the subpolar gyre and communicated southwards into the subtropical gyre 32,86 , either slowly through advection of deep subpolar density anomalies 87 , or more quickly through boundary waves 86,88,89 . There is strong mixing of these dense waters before reaching the subtropics [90][91][92] , meaning that perhaps only large and persistent AMOC anomalies succeed in being communicated southwards 93,94 .…”
Section: Southward Communication Of Amoc Anomaliesmentioning
confidence: 99%
See 2 more Smart Citations
“…While many AMOC anomalies remain localized, some are communicated meridionally, giving rise to large-scale AMOC variations. Large-scale AMOC anomalies are thought to be generated in the subpolar gyre and communicated southwards into the subtropical gyre 32,86 , either slowly through advection of deep subpolar density anomalies 87 , or more quickly through boundary waves 86,88,89 . There is strong mixing of these dense waters before reaching the subtropics [90][91][92] , meaning that perhaps only large and persistent AMOC anomalies succeed in being communicated southwards 93,94 .…”
Section: Southward Communication Of Amoc Anomaliesmentioning
confidence: 99%
“…However, the strong subpolar AMOC in the mid-1990s has also been linked to a strong subtropical AMOC in the late 1990s, with a faster propagation time 30,112 . Although some models also suggest meridional linkages of AMOC variability [86][87][88] , the processes and timescales vary, and it might be that some subpolar signals do not reach the subtropics 90,91,93 .…”
Section: Subtropical Amocmentioning
confidence: 99%
See 1 more Smart Citation
“…Further exploration is needed before a specific attribution for the large transformation in winter 2014-2015 is made, however we do note that a number of recent papers have documented strong advective changes in the Iceland Basin over the past few years. In one study (Ortega et al, 2020) the NAC is shown to drive large salinity and temperature property changes at the surface and subsurface, while in another study (Holliday et al, 2020), strong property changes are attributed to changes in the fraction of water from the Labrador Sea that reaches the Iceland Basin. These studies, highlighting the importance of ocean advection, are consistent with a previous paper that showed large hydrographic property changes for SPMW localized over the Reykjanes Ridge that cannot only be explained by the variability of the local air-sea fluxes (Thierry et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The Atlantic Meridional Overturning Circulation (AMOC) is pointed out as a key source of decadal to multidecadal climate predictability in the SPNA. However, recently the Labrador Sea Water thickness anomalies have been indicated as precursor of upper ocean heat content predictability in this area, as well as an important driver influencing the southward ocean circulation (Ortega et al, 2020;Yeager, 2020). The Labrador Sea Water is formed by convective processes driven by high oceanic heat losses during winter.…”
Section: Discussionmentioning
confidence: 99%